Przesłanki teoretyczne integracji gospodarczej i jej znaczenie dla kształtowania polityki handlowej - Domiter, Małgorzata (Theoretical Premises of Economic Integration and its Importance for the Trade Policy Shaping, 2005)
The integration theory and the closely related theories of customs union, single market and monetary union constitute organic parts of the foreign trade theory. The scope of economic integration theory is almost identical with the scope of the international trade theory. The economic integration theory may be considered part of the International Economics. Simultaneously, it also covers part of the international trade theory since it analyses the scale of the impact of united national markets on the growth and co-ordination of the union's economic policy. In practice, any form of integration is, essentially, a trade integration. Along with the onset of liberalization tendencies in economy, especially with regard to trade, the economic integration and its effects for international trade must be subject to the regulations of GATT/WTO.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 62-75